ANALISIS EFISIENSI PENGGUNAAN MODAL KERJA PADA KOPERASI TUNAS MELATI DI SD MUHAMMADIYAH 1 SAMARINDA - Osi Putri Fatmawati; Yulia Tri Kusumawati (Universitas Muhammadiyah Kalimantan Timur, 2017)
Working capital is a capital used to financing operational of the company day by day. Controling working capital with effective and efficient is needed to improve liquidity and maximize profits. The purpose of this study is measuring the efficiency of working capital utilization Tunas Melati cooperative in SD Muhammadiyah 1 Samarinda, in period 2012 - 2016 viewed by the level of liquidity, activity, and profitability.Research data obtained by interviewing techniques, documentation, and litteraure study. Data in the form of a balance sheet financial statement and profit loss report are analyzed using liquidity ratio, activity ratio, and profitability ratio.The results of research, showed that the use of working capital in Tunas Melati cooperative during the period 2012 - 2016 viewed from the liquidity ratio is efficient with the current ratio of 154%, 208%, 174%, 204%, 253% and the fast ratio of 146%, 191% , 160%, 185%, 224%; in terms of activity ratio is not efficient with account receivable turnover rate of 2.3 times, 2.4 times, 2.1 times, 2.1 times, 1.9 times, inventory turnover of 26.1 times, 20.8 times , 16.3 times, 14.2 times, 8.6 times, and working capital turnover of 1.4 times, 1.4 times, 1.3 times, 1.2 times, 0.9 times; in terms of profitability ratios is efficient with 21%, 21%, 24%, 22%, 24% return on assets and equity returns of 60%, 40%, 55%, 43%, 39%.